The Personal Entrepreneurial Competencies (PECs) of the BS in Entrepreneurship Students Batch 2016 of the Mariano Marcos State University, City of Batac, Ilocos Norte, Philippines - C. Sabugo, Armie; C. Barot, Reena Gilaine; B. Julian, Charito (International Journal of Management and Education in Human Development, 2023)
Entrepreneurship education plays a significant role in economic development. Moreover, it is a driving force to encourage students to start and manage their businesses by honing their entrepreneurial competencies. The Bachelor of Science in Entrepreneurship of the Mariano Marcos State University, however, struggles to produce graduates who engage in business because they prefer to be employed. Given the premise that entrepreneurship education influences the development and improvement of students' competencies, the researchers probed on the students' Entrepreneurial Competencies (PECs) improved after four years of exposure to entrepreneurship education, as well as the significant difference between their PECs in 2012 and 2016. This study used quantitative research. A questionnaire was designed to elicit the socio-demographic and economic profile of the student respondents. The PECs survey questionnaire, which was adapted from the MSI and McBer Team questionnaire, was used to gather data regarding the PEC profile of the students. The results of the study revealed that the students’ PECs improved in 2016, especially along goal setting. Risk-taking and systematic planning and monitoring however did not have a significant difference.